INTERNATIONAL MARKET SELECTION FOR FROZEN SHRIMP EXPORTS FROM THAILAND: AN INTEGRATION OF CAGE DISTANCE FRAMEWORK AND DATA ENVELOPMENT ANALYSIS - Inkaew, Amondech; Phokawattana, Onpawee (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2024)
Purpose – This research aims to assess and rank the efficiency of countries where Thailand exported frozen shrimp to, and to provide actionable insights for policymakers and stakeholders in the frozen shrimp export industry based on the efficiency scores. Methodology – This study employed the integration of the CAGE Distance Framework and Data Envelopment Analysis (DEA) to investigate the dynamics of international market selection for frozen shrimp exports from Thailand. The study evaluated and ranked the effectiveness of 20 nations that were chosen based on 2022 export values exceeding 1,000,000 US Dollars. The DEA BCC model, utilizing linear programming techniques, categorized these countries as Decision Making Units (DMUs), assessing their efficiency to determine how efficiently a DMU produced outputs given a set level of inputs. Results – Results from the DEA analysis highlighted efficiency leaders with an efficiency score of 1, such as China, the United States, Japan, Taiwan, Hong Kong SAR, Australia, Myanmar, Vietnam, Singapore, Cambodia, and Laos. Additionally, it identified intermediate performers with room for improvement and countries with opportunities for optimization. Implications – This integrated methodology served as a valuable guide for future students and professionals navigating the complexities of the global frozen shrimp trade. Originality/Value – The integration of the CAGE framework with DEA offered a unique approach that had not been explored in previous applications. It established a pioneering approach for policymakers, practitioners, and entrepreneurs.